1990
DOI: 10.1152/ajpendo.1990.258.1.e40
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin receptors and vagal nerves in control of food intake in rats

Abstract: This study was designed to determine the specificity and physiological nature of short-term satiety effects of cholecystokinin (CCK) in rats with intact and transected vagal nerves. Rats with-the gastric fistulas, closed or open, were used for normal feeding or sham feeding of liquid meal offered for 30 min. CCK-8 (0.5-10 nmol/kg) injected intraperitoneally (ip) 15 min before feeding inhibited food intake dose dependently in both normal-fed and sham-fed rats at a minimal inhibitory dose of 1 nmol/kg. CCK-8 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 10 publications
4
23
0
Order By: Relevance
“…We showed that 1 and 10 nmol/kg CCK significantly reduced food intake in naive rats 0.5, 1, and 2 h after ip injection, whereas 0.1 nmol/kg CCK administered ip did not decrease food intake. Consistent with our findings, some studies have shown that the threshold dose of CCK for reduction of food intake in rats is 1 nmol/kg (17,18). Interaction between leptin and CCK reduces short-term food intake (3,39,56).…”
Section: Discussionsupporting
confidence: 92%
“…We showed that 1 and 10 nmol/kg CCK significantly reduced food intake in naive rats 0.5, 1, and 2 h after ip injection, whereas 0.1 nmol/kg CCK administered ip did not decrease food intake. Consistent with our findings, some studies have shown that the threshold dose of CCK for reduction of food intake in rats is 1 nmol/kg (17,18). Interaction between leptin and CCK reduces short-term food intake (3,39,56).…”
Section: Discussionsupporting
confidence: 92%
“…The time needed to inject rats was ϳ30 s/rat. The dose of CCK was based on previous studies showing a robust reduction of food intake following injection of 2 nmol/kg CCK-8 (17,56). Experiments were repeated in a crossover design in the same batch of rats for each treatment.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the completeness of the vagotomy, a food intake analysis was performed based on the satiety effect of cholecystokinin-octapeptide (CCK-8) (Sigma Aldrich, St. Louis, MO), which is known to be mediated by the afferent vagus nerve (7,14). All animals were food deprived for 20 h and then received an injection (ip) of 8 g CCK ⅐ kg Ϫ1 ⅐ mouse Ϫ1 , and their 2-h food intake was measured.…”
Section: Methodsmentioning
confidence: 99%